Factors Influencing Reproductive Health Behavior in Adolescents at Wirakarya 2 SHS, Ciparay - Puspa Wati Manik, Tri Arini; Mulyani, Neng; Khairunnisa, Ika; Ajeng, Ajeng; Nurrahmawati, Suci (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescence is a critical period in the development of reproductive health. Improper reproductive health behaviours can lead to a variety of long-term problems. Objective: This study aims to analyse the factors that affect reproductive health behaviour in vocational school adolescents. Method: This study uses a quantitative approach with a cross-sectional design. The research sample was 125 students of SMK Wirakarya 2 Ciparay who were selected using stratified random sampling. The research instrument is in the form of a structured questionnaire to measure knowledge, attitudes, and reproductive health behaviours. Data analysis uses Chi-square test and Odds Ratio calculation. Result and Discussion: This study was obtained from respondents who had sufficient knowledge (46.4%), positive attitudes (54.4%), and positive behaviours (56.8%). There was a significant relationship between knowledge and reproductive health behaviours (p=0.011; OR=2.404) and a very significant association between attitudes and reproductive health behaviours (p=0.001; OR=3,809). Attitude is the most dominant factor influencing adolescent reproductive health behaviour. Conclusion: Knowledge and attitudes play a significant role in shaping adolescent reproductive health behaviours. Attitude has a stronger influence than knowledge. A comprehensive educational program is needed that not only increases knowledge but also forms a positive attitude towards reproductive health.